Does breastfeeding account for the association between maternal sensitivity and infant cognitive development in a large, nationally representative cohort? - P. Nina Banerjee; Karen E. McFadden; Jacqueline D. Shannon; Leslie L. Davidson (BMC, 2022)
Abstract Background Previous research has established that exposure to high maternal sensitivity is positively associated with advances in infant cognitive development. However, there are many fixed and modifiable factors that influence this association. This study investigates whether the association between maternal sensitivity and infant cognitive development in the first year of life is accounted for by other factors, such as breastfeeding, maternal depressive symptoms, maternal alcohol use, infant birth weight or demographic covariates. Methods Using data from the Early Childhood Longitudinal Study-Birth (ECLS-B) Cohort, a nationally representative sample of U.S. born children, multi-variable regression analyses was used to examine whether breastfeeding, maternal depressive symptoms and alcohol use were associated with maternal sensitivity, as measured by the Nursing Child Assessment Teaching Scale (NCATS), and with infant cognitive development, as measured by the Bayley Scales of Infant Development, Short Form, Research Edition, after controlling for demographic covariates (infant sex, maternal age, education, race/ethnicity, income, parity, family structure) and infant birth weight. Results Breastfeeding, depressive symptoms and alcohol use were not associated with maternal sensitivity scores after controlling for demographic covariates and infant birth weight. However, breastfeeding (β = .079, p < .001), depressive symptoms (β = −.035, p < .05), and maternal sensitivity (β = .175, p < .001) were each significantly associated with infant cognitive development scores, even after controlling for demographic covariates and birthweight (R2 = .053, p < .001). The association between maternal sensitivity and infant cognitive development did not attenuate after adjusting for breastfeeding. Instead, both sensitivity and breastfeeding independently contributed to higher infant cognitive development scores. Conclusion Maternal sensitivity and breastfeeding are separate means to advancing infant cognitive development. This study is significant because it is the first to examine breastfeeding, maternal depressive symptoms and alcohol use together, upon the association between maternal sensitivity and infant cognitive development, after adjusting for demographic covariates and infant birthweight. Maternal sensitivity, a measurable quality, advances infants' cognitive development. Moreover, sensitivity and breastfeeding had independent effects upon cognitive development after controlling for multiple fixed and modifiable covariates. Understanding factors impacting the association between sensitivity and infant cognitive development provide avenues for developing more effective parenting interventions.